The Imagined Geography in the Philology of Erich Auerbach - Angelov, Angel (Pitannâ lìteraturoznavstva, 2020)
The purpose of the author is to find the main motive why Auerbach chose to use the non-disciplinary term “European philologists” and what he meant by that. I argue that Auerbach’s consciousness of Europe as a historical entity was formed in the 1920s, but his exile turned this consciousness into a position. A basic question is about the symbolic geography of European culture in the works of Auerbach. The synonymous use of Europe and Abendland distinctly reveals Auerbach’s dual, unifying/divisive understanding of the identity and symbolic geography of European culture. If we accept the opinion that the European has been represented for centuries by the Romance, then the tasks of Romance philology as European philology will become clearer and the cultural geography of Europe narrower. The cultural-historical identification of Europe and Abendland after the Second World War solidified the anyway existing division of Europe in to two blocs. Literary history and philology divided Europe in the way this was done by the relevant political doctrines too. The human sciences also contributed significantly to the creation of value-attitudes, and an investigation of the former from this perspective gives us additional reason to assume that the agreement on the division of Europe after the Allied victory was not based solely on strategic interests.